PERAN SERTA MASYARAKAT KABUPATEN BALANGAN DALAM PENGELOLAAN SAMPAH RUMAH TANGGA DI BANTARAN SUNGAI - Muhammad Rasid Rida; Emmy Sri Mahreda; Hafizianor3 Hafizianor3; Rizqi Puteri Mahyudin (EnviroScienteae, 2021)
This study aims to analyze the management of household waste on riverbanks, community participation in the management of household waste on riverbanks, and analyze the factors that influence the management of household waste on riverbanks. of rivers and community involvement in Balangan Regency. This study uses a quantitative social approach. Quantitative social method, sampling in three villages using proportional random sampling and data collection using a questionnaire that was analyzed using a simple linear regression test. According to the results of the analysis in three villages, the waste management has been implemented correctly. Based on the analysis of community participation that the average respondent answered a role, it can be seen in the results of the response of each respondent in which the community variable is 82.13% and the management variable is 78.10%. Based on the results of the t-test, it can be seen that the community obtained a t-count value of 3.626 with a significance level of 0.001. This shows that the level of significance of the community is less than 0.1, so statistically the influence is very large or it is said that there is a significant community influence in the management, so the hypothesis is accepted. Based on the calculation of the regression test, it can be seen that the value of the t count is 3.626> t table 1.67065 according to the criterion if t count> t table then there is a significant positive influence of the community in the management.